An Extended Boarding Strategy Accounting for the Luggage Quantity and Group Behavior. (3rd February 2019) - Tang, Tie-Qiao; Yang, Shao-Peng; Chen, Liang
Abstract : The reasonable boarding strategy can enhance the efficiency, so how to enhance the boarding efficiency has been a hot topic in the air transportation. In this paper, we incorporate the luggage quantity and the passenger's group behavior into the boarding model, and develop an extended strategy to explore each passenger's boarding behavior and the influences of the proposed strategy on the boarding efficiency. The numerical results indicate that the proposed strategy can relieve the congestions at the wicket and in the cabin, eliminate the seat conflicts, and reduce the time of handling luggage and the boarding time. This shows that the proposed strategy can enhance the boarding efficiency. The results can help administrators organize the boarding pattern to enhance the efficiency.